The impact of monopoly power, and asymmetric information to adopt E-procurement - Habiburrochman, Siti Fatimah, (Opción, 2020)
Information and Communication Technology (ICT) offers a new approach for private organizations, governments and other institutions. This study aims to determine the effect of monopoly power, asymmetric information, transparency and accountability on the intention to adopt E-Procurement. The results suggest that e-procurement has the potential to limit the risk of corruption by reducing the monopoly power of public officials, reducing asymmetric information in the process of procurement of public goods and services electronically and increasing transparency and accountability in the process of procurement of goods and services, thus affecting the intention to adopt e-procurement at state universities in Surabaya.